Use of Probemix and OmniProbe biotinylated cDNA probes for detecting HPV infection in biopsy specimens from the genital tract. Issue 5 (May 1993) - Zehbe, I; Rylander, E; Strand, A; Wilander, E
Abstract : AIMS–To compare two commercially available pan probes for the identification of human papillomavirus (HPV) DNA expression in histological sections and to type the HPV positive cases. METHODS–97 formalin fixed, paraffin wax embedded biopsy specimens from the genital tract were tested for HPV positivity with in situ hybridisation using biotinylated cDNA pan probes–Probemix (Enzo) and OmniProbe (Digene). The HPV positive cases were further tested with HPV types 6/11, 16/18, and 31/33/35/51, and the HPV type was related to the histological diagnosis. Formalin fixed, HeLa cells (10-50 HPV 18 copies per cell) and SiHa cells (1-2 HPV 16 copies per cell) were used as reference cell lines. RESULTS–32% of the specimens gave positive nucleic signals with both Probemix and OmniProbe. Of these, 84% could be further characterised with regard to HPV types 6/11, 16/18, and 31/33/35/51; 4% of all cases were positive with either Probemix or OmniProbe. The concordance of these probes was high, 96% altogether. HeLa cells stained positive but SiHa cells did not. CONCLUSION–There is no difference between Probemix and OmniProbe for the general detection of HPV. The mean detection limit of these probes is about 20 copies a cell.